Duration of the hypotensive effect of modified transscleral cyclophotocoagulation in patients with diabetic neovascular glaucoma (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To determine the duration of the hypotensive effect of the modified transscleral cyclophotocoagulation (TSCPC) with an 810-nm laser (1.5 J/ pulse) versus a 1064-nm laser (1.0 J/ pulse) followed by a 12-month follow-up in patients with diabetic neovascular glaucoma (NVG), and to assess the need for repeat TSCPC.Material and Methods: This prospective open-label study included patients with diabetic NVG with a follow-up of 12 months. Proliferative diabetic retinopathy (DR) was found in 31/46 patients (67%) and the fundus could not be visualized in 15/46 patients (33%). Nine patients (20%) had a history or retinal laser photocoagulation and no pattern vision. All patients received TSCPC with a diode laser (810 nm, 1.5 J/ pulse) or neodymium:yttrium-aluminum-garnet (Nd:YAG) laser (1064 nm, 1.0 J/ pulse). TSCPC success was defined as an IOP between 10 and 21 mmHg (or a reduction in IOP of ≥ 30% from baseline IOP), no ocular pain, and an improvement or no change in best-corrected visual acuity.Results: There was no statistically significant difference (р = 0.87) in the duration of hypotensive effect in NVG patients between diode-laser TSCPC and Nd:YAG-laser TSCPC. At 12 months, IOP was ≤ 21.0 mmHg in eyes of 18/24 patients (75%) in group 1 (1064 nm) versus 17/22 patients (75%) in group 2 (810 nm). The regression model for predicting the need of repeat TSCPC in diabetic patients with NVG based on baseline IOP, presence of ocular complications of NVG, and ocular pain score and diabetes duration explained 94% of the variation in outcome (Nagelkerke's R2 = 0.94), and the model accuracy, sensitivity and specificity were 96.2% (p < 0.001), 0.958 and 0.882, respectively.Conclusion: At 12 months, stable ocular hypotensive effect of the modified TSCPC with an 810-nm laser (1.5 J/ pulse) and a 1064-nm laser (1.0 J/ pulse) was observed in 77% and 75%, respectively, of diabetic patients with NVG. The independent variables with the largest impact on the need for repeat TSCPC in diabetic patients with NVG were the baseline pain numeric rating scale score ≥ 8 (odds ratio (OR), 4.0; 95% confidence interval (CI), 1.84-8.91), presence of ocular complications (OR, 3.02; 95% CI, 1.84-8.91), diabetes duration ≥7 years (OR, 2.03; 95% CI, 1.46-2.28) and IOP ≥35 mmHg (OR, 1.16; 95% CI, 1.4-3.3).
Keywords: diabetes mellitus; proliferative diabetic retinopathy; neovascular glaucoma; retina; ciliary body; cyclophotocoagulation